Effects of the Crocus sativus L. Extract on the Acquisition and Expression of Morphine-Induced Conditioned Place Preference in Female Mice - H Sahraei; M Mohammadi; M Kamalinejad; J Shams; H Ghoshooni; A Noroozzadeh (Institue of Medicinal Plants, ACECR, 2008)
Background: Experiments indicated that Crocus sativus L. extract may have an interaction with morphine. The effects of C. sativus on the euphoric properties of morphine in female mice did not studied. Objective: In the present study, the effects of water extract of C. sativus stigma on the acquisition and expression of morphine-induced conditioned place preference (CPP) in female N-MARI mice (20-25 g) were investigated. Methods: This experimental study was conducted on the 136 female fice that were divided in 17 groups (n=8/group). In a pilot study, different doses of morphine (1, 10 and 20 mg/kg) and the extract (10, 50 and 100 mg/kg) were injected to the animals for evaluation of the drugs ability to induction of place preference. In the second phase of the experiments, the extract of the C. sativus was administered during or after induction of morphine CPP. Then, CPP were tested in the animals. One-way Analysis of Variance (ANOVA) was proformed for statistical procedure. Results: Administration of morphine (1, 10 and 20 mg/kg), indcreased the time spend in the compartment paired with morphine (i.e. conditioned place preference-CPP). The increament was significant for the dose 10 and 20 mg/kg of morphine. Administration of the plant extract (50 mg/kg) also produced a significant CPP. Injection of the same doses of the extract before morphine (10 mg/kg) administration, caused a decrease in the time spent in drug-paired side in doses 50 and 100 mg/kg of the extract. In addition, injection of the plant extract in the test day to the animals in which reveived morphine (10 mg/kg) in the conditioning days decreased the expression of morphine CPP in the animals which was statisticaly significant for dose 10 mg/kg of the extract. Conclusion: It could be concluded that injection of the extract of C. sativus can inhibit the acquisition and expression of morphine-induced CPP. In addition, the extract produced CPP in female mice by it-self. These results indicated that saffron extract might be useful in morphine-induced psychological dependence in human as well.